Risk of Coronavirus Disease 2019 Messenger RNA Vaccination-Associated Myocarditis and Pericarditis – A Systematic Review of Population-Based Data - Lin YC; Chang CH; Su WJ; Yang CH; Wang JT (Dove Medical Press, 2023)
Yen-Ching Lin,1,* Chia-Hsuin Chang,1- 3,* Wei-Ju Su,4,5 Chin-Hui Yang,4 Jann-Tay Wang1,2 1Department of Medicine, College of Medicine, National Taiwan University, Taipei, Taiwan; 2Department of Internal Medicine, National Taiwan University Hospital, Taipei, Taiwan; 3Institute of Epidemiology and Preventive Medicine, College of Public Health, National Taiwan University, Taipei, Taiwan; 4Centers for Disease Control, Ministry of Health and Welfare, Taipei, Taiwan; 5Department of Pediatrics, National Taiwan University Hospital, Taipei, Taiwan*These authors contributed equally to this workCorrespondence: Chia-Hsuin Chang, Department of Internal Medicine, National Taiwan University Hospital, 7, Chung-Shan South Road, Taipei, 100, Taiwan, Tel +886-2-23123456, Fax +886-2-2392-0456, Email chiahsuin@yahoo.comPurpose: Early studies showed that the risks of mRNA vaccine-associated myocarditis and pericarditis are low but with substantial variation across studies. Study characteristics, ethnicity, vaccine types, dose intervals, and SARS-CoV-2 infection prevalence may influence the rates of myocarditis and pericarditis after mRNA vaccination in population-based studies.Methods: We comprehensively searched MEDLINE for relevant articles published before November 30, 2022. We also searched the websites of health authorities in several countries for unpublished surveillance data on myocarditis and pericarditis after mRNA vaccination. The outcome of interest was the incidence of myocarditis and pericarditis developed after mRNA vaccination for COVID-19.Results: A total of 17 studies form 10 countries were included for review. We noted that considerable heterogeneity in study characteristics, including surveillance method, case definition, and observation period, may partially be responsible for the widely varied reported rates. Studies from countries that adopted active surveillance reported higher rates than those using passive surveillance. Compared to BNT162b2 vaccine, mRNA-1273 may have a higher risk of myocarditis only in young men after the second dose. Our comparison of sex-, age-, vaccine type-, and dose-specific rates of myocarditis across countries did not support the hypothesis that individuals with recent SARS-CoV-2 infection and young Asian males were at higher risk. We also could not find sufficient evidence to conclude whether extending the between-dose interval could reduce myocarditis incidence following mRNA vaccination.Conclusion: Differences in the study characteristics must be fully considered when comparing the risks of mRNA vaccine-related myocarditis and pericarditis in different countries.Keywords: COVID-19, mRNA vaccine, myocarditis, population-based study, surveillance data